1997
DOI: 10.1074/jbc.272.23.14805
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Tetrodotoxin-sensitive, Voltage-gated Sodium Channel Expressed in Rat and Human Dorsal Root Ganglia

Abstract: Dorsal root ganglion neurons express a wide repertoire of sodium channels with different properties. Here, we report the cloning from rat, dorsal root ganglia (DRG), cellular expression, and functional analysis of a novel tetrodotoxin-sensitive peripheral sodium channel (PN), PN1. PN1 mRNA is expressed in many different tissues. Within the rat DRG, both the mRNA and PN1-like immunoreactivity are present in small and large neurons. The abundance of sodium channel mRNAs in rat DRG is rBI > PN1 PN3 >>> rBIII by q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
168
2
4

Year Published

1998
1998
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 256 publications
(187 citation statements)
references
References 38 publications
11
168
2
4
Order By: Relevance
“…DRG is composed of heterogeneous cell types that were shown to differ in their expression patterns of CACNA1B transcripts. Similar observations were made with SCN9A transcripts in rat DRG (35). In this study, we have treated DRG as a homogeneous tissue and detected a diverse spectrum of alternative splicing.…”
Section: Discussionsupporting
confidence: 81%
“…DRG is composed of heterogeneous cell types that were shown to differ in their expression patterns of CACNA1B transcripts. Similar observations were made with SCN9A transcripts in rat DRG (35). In this study, we have treated DRG as a homogeneous tissue and detected a diverse spectrum of alternative splicing.…”
Section: Discussionsupporting
confidence: 81%
“…Initial studies of Na v 1.7 channels expressed in Xenopus oocytes indicated that the ␤ 1 and ␤ 2 subunits failed to alter the expression or gating properties of Na v 1.7, suggesting that these channels may be not regulated by these auxiliary subunits (27,28). Subsequent work, also in oocytes, found that coexpressing ␤ 1 accelerated inactivation and recovery kinetics and produced a hyperpolarizing shift in Na v 1.7 activation (29).…”
Section: Discussionmentioning
confidence: 99%
“…The second step is initiation of action potentials in the nociceptors by voltage-gated sodium channels (VGSCs). Among the 10 VGSC isoforms, two, Na v 1.8 (Akopian et al, 1996;Sangameswaran et al, 1997) and Na v 1.9 (Dib-Hajj et al, 1998;Tate et al, 1998), are expressed almost exclusively by small nociceptor primary afferent neurons (Amaya et al, 2000) and are tetrodotoxin insensitive. Na v 1.8 generates a tetrodotoxin-resistant (TTXr) current with a threshold of activation of Ϫ40 mV that inactivates slowly (TTXrSlow) (Akopian et al, 1996;Sangameswaran et al, 1997;Renganathan et al, 2002b;John et al, 2004), whereas Na v 1.9 is presumed from recordings in Na v 1.8 null mice, to produce a persistent current with a more hyperpolarized voltage dependence and ultraslow recovery from inactivation (TTXr-Per) Baker et al, 2003).…”
Section: Introductionmentioning
confidence: 99%